Does Immigration into Their Neighborhoods Incline Voters Toward the Extreme Right? The Case of the Freedom Party of Austria - Martin Halla; Alexander F. Wagner; Josef Zweimüller (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
This paper explores one potentially important channel through which immigration may drive support for extreme right-wing parties: the presence of immigrants in ones neighborhood. We study the case of the Freedom Party of Austria (FPÖ). Under the leadership of Jörg Haider, this party increased its share of votes from less than 5 percent in the early 1980s to 27 percent by the year 1999. Using past regional settlement patterns as a source of exogenous variation, we find a significantly positive effect of the residential proximity of immigrants on FPÖ votes, explaining roughly a quarter of the cross-community variance in FPÖ votes. It is the presence of low- and medium-skilled immigrants that drives this result; high-skilled immigrants have no (or even a negative) effect on FPÖ votes.
Keywords: P16; J61; 330; Immigration; political economy; voting